Editors’ Introduction. Futures: Imagining the World of Tomorrow - Tibaldeo, Roberto Franzini; Rebuffo, Cristina; Maggio, Luisa (ETHICS IN PROGRESS, 2017)
From 12 to 17 September 2016 in Cuneo (Italy) took place the 9th edition of the international Summer School organized by the Centro Studi sul Pensiero Contemporaneo (CeSPeC). The event revolved around the topic of the “future”, which was analysed from different interdisciplinary perspectives and gave rise to stimulating conversation. In this introduction we provide an overview of the topic and of the reflections stemming from that event.